Biomarkers in the Pathogenesis of Heart Failure with Preserved as Well as Reduced Ejection Fraction: A Cross-sectional Study - Sowmiya Thiyagarajan; Jasmine Chandra A.; Karthikeyan Rajamani; Santhi Silambanan (International Journal of the Cardiovascular Academy, 2025)
Background and Aim: Heart failure (HF) is a multifaceted cardiovascular condition characterized by various pathophysiological mechanisms that lead to impaired ventricular structure or function. Diagnosing HF with preserved ejection fraction (HFpEF) and reduced EF (HFrEF) presents significant challenges due to overlapping symptoms and distinct underlying causes. This study aimed to investigate metabolic and inflammatory markers in patients with HFrEF and HFpEF. Materials and Methods: The study included 80 HF patients, comprising HFpEF (n=40) and HFrEF (n=40), aged 30-90 years, of both genders. Participants were recruited from the department of cardiology at a tertiary care hospital. Blood samples were collected to analyze biomarker levels and statistical analysis was conducted considering a P-value of ≤0.05 as statistically significant. Results: Patients with HFpEF had lower levels of total cholesterol, plasma glucose, glycated hemoglobin, N-terminal pro brain natriuretic peptide (NT-proBNP), and high sensitivity C-reactive protein (hsCRP), compared to those with HFrEF. There were significant differences in echocardiography variables when compared among the groups. hsCRP showed a cut-off value of 3.15 mg/L, whereas NT-proBNP showed 437.8 pg/mL. Conclusion: The study identified notable differences in metabolic and inflammatory marker profiles between HFpEF and HFrEF patients. HFpEF was associated with less severe dyslipidemia and inflammation, as indicated by lipid profiles, NT-proBNP and hsCRP levels, compared to HFrEF. Understanding these biomarker variations may aid in developing personalized treatment strategies and enhancing patient care.